Analisis pendapatan nelayan pukat cincin dan huhate di Pelabuhan Perikanan Samudera Kendari - Mui'z, Rifal; Nurdiana A; Abdullah; Yusuf, Sarini; Kamri, Syamsul (Universitas Halu Oleo, 2024)
This study aimed to determine the income of purse seine and pole and line fishing businesses at The Ocean Fishing Port in Kendari. This research was carried out from August to September 2023. The variables used in this research were input, output, costs, receipts and income. This experiment used a purposive sampling method with the number of respondents being 1 purse seine and 1 huhate respondent. Data was obtained through observation, interviews, questionnaires and documentation. The analysis used were total costs, revenues and profits. The results of the analysis showed that the average purse seine income was IDR 22,642,421/trip, while huhate was IDR 12,626,213/trip. This study concluded thatt huhate (pole and line fishing) income was higher than purse seine